Discovery of benzethonium chloride as a potent STAT3 inhibitor for the treatment of HNSCC - Han, Yuefeng; Li, Shumin; Chen, Deshang; Zhang, Mingjie; Han, Guoying; Xu, QianQian; Ge, Xianming; Wang, Mengli; Pan, Yan; Ma, Sien; Xu, Beibei; Deng, Mengmeng; et al. (Frontiers in Pharmacology, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a prevalent malignancy with high mortality, and effective treatment strategies remain limited. This study investigated the effects of benzethonium chloride (BZN), an FDA-approved anti-infective agent, on HNSCC cell lines and its underlying mechanisms. BZN significantly inhibited the proliferation of HNSCC cell lines CAL27 and FaDu and induced apoptosis in both cell lines in vitro. In a subcutaneous tumor model, BZN markedly suppressed tumor growth in the mouse HNSCC cell line MOC1. Mechanistically, BZN may directly bind to the SH2 domain of STAT3, inhibit its dimerization, prevent the nuclear translocation of phosphorylated STAT3 (p-STAT3), downregulate the expression of the downstream protein MCL-1, and induce mitochondrial-mediated apoptosis in FaDu and CAL27 cells. These findings highlight BZN as a potential therapeutic agent for HNSCC, offering a novel approach to improve treatment outcomes in clinical settings.